Penerapan Konsep Good Coorparate Governance Dalam Dunia Usaha Di Indonesia - Aritonang, Dinoroy M (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
One of the urgent programs of the national development program in Indonesia is restructuring bussiness competence (market based on competition), which a has been undermanaged in this matter, management models will give the best impact for our corporation or especially Stated Owned Entreprises. Learning from this, one of the good way to rebult or recreate our management models is Good corporate Governance, Implemeneted in corporate structure level, internal and external regulation, more power in controlling and punisment, and integrated-independent-proffesional management teamwork.